Two-photon widths of the χcJ states of charmonium - Ecklund, K; Love, W; Savinov, V; Lopez, A; Mendez, H; Ramirez, J; Ge, J; Miller, D; Shipsey, I; Xin, B; Adams, G; Anderson, M; et al. (2008)
Using a data sample of 24.5×106 ψ(2S) the reactions ψ(2S)→γχcJ, χcJ→γγ have been studied for the first time to determine the two-photon widths of the χcJ states of charmonium in their decay into two photons. The measured quantities are B(ψ(2S)→γχc0)×B(χc0→γγ)=(2. 17±0.32±0.10)×10-5 and B(ψ(2S)→γχc2) ×B(χc2→γγ)=(2.68±0.28±0.15)×10-5. Using values for B(ψ(2S)→γχc0,c2) and Γ(χc0,c2) from the literature the two-photon widths are derived to be Γγ γ(χc0)=(2.36±0.35±0.22)keV, Γγγ(χ c2)=(0.66±0.07±0.06)keV, and R≡Γγγ(χ c2)/Γγγ(χc0)=0.278±0.050±0.036. The importance of the measurement of R is emphasized. For the forbidden transition, χc1→γγ, an upper limit of Γγγ(χc1) <0.03keV is established. © 2008 The American Physical Society.